Lemon Aromatherapy for Reducing Anxiety in Pregnant Women Approaching Labor - Pujiati, Wasis; Julia DS, Hotmaria; Nirnasari, Meily; Sari, Komala; Wati, Liza; Kurniati, Safra Ria; Sartika, Lili; Arianingsih, Tri; Asnita, Asnita; Trisnawati, Yeti (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Anxiety in pregnant women before childbirth was often caused by hormonal changes that affected emotional states. This study aimed to evaluate the effect of lemon aromatherapy on anxiety levels in pregnant women approaching labor. A quasi-experimental method was used with a pre-test and post-test with control group design, involving 32 pregnant women in the working area of Kampung Bugis Public Health Center. Data analysis using the Wilcoxon test showed that the administration of lemon aromatherapy significantly reduced anxiety levels, with a p-value of 0,000. This study recommended lemon aromatherapy as a safe and effective non-pharmacological method to reduce anxiety in pregnant women prior to childbirth.